2013
DOI: 10.1371/journal.pone.0060943
|View full text |Cite
|
Sign up to set email alerts
|

Src Regulates the Activity of the ING1 Tumor Suppressor

Abstract: The INhibitor of Growth 1 (ING1) is stoichiometric member of histone deacetylase (HDAC) complexes and functions as an epigenetic regulator and a type II tumor suppressor. It impacts cell growth, aging, apoptosis, and DNA repair, by affecting chromatin conformation and gene expression. Down regulation and mislocalization of ING1 have been reported in diverse tumor types and Ser/Thr phosphorylation has been implicated in both of these processes. Here we demonstrate that both in vitro and in vivo, the tyrosine ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…al. reported that Src phosphorylated the HDAC Inhibitor of Growth 1 (ING1), resulting in nuclear to cytoplasmic localization and decrease in protein stability (44) . C-terminal Src kinase (Csk)-binding protein (Cbp)/PAG1 expression was repressed via Src-mediated alterations in histone H4 acetylation and trimethylation of histone H3/lysine 27 in the Cbp promoter and associated changes in HDAC activity (45).…”
Section: Discussionmentioning
confidence: 99%
“…al. reported that Src phosphorylated the HDAC Inhibitor of Growth 1 (ING1), resulting in nuclear to cytoplasmic localization and decrease in protein stability (44) . C-terminal Src kinase (Csk)-binding protein (Cbp)/PAG1 expression was repressed via Src-mediated alterations in histone H4 acetylation and trimethylation of histone H3/lysine 27 in the Cbp promoter and associated changes in HDAC activity (45).…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al (17) demonstrated that immunostaining for ING2 was mostly located to the cytoplasm, while weak nuclear staining was also observed in HCC tissues and normal hepatocytes, in line with a study by Gozani et al (5), who reported that phosphatidylinositol 5-phosphate 4-kinase type II β expression decreased endogenous nuclear ING2 in HT1080 fibrosarcoma cells. It has been reported that ING1 phosphorylation by 14-3-3 family members (23) or Src (24) caused its cytoplasmic re-localization leading to apoptotic induction. Future studies should investigate the purpose of ING2 restoration in the cytoplasm as well as its function.…”
Section: Discussionmentioning
confidence: 99%
“…Src destabilizes ING1 by phosphorylation, thereby inducing its export from nucleus. The Src phosphorylation-independent mechanism is based on the capacity of Src to bind directly ING1: in this role as cofactor, Src may prompt the degradation of ING1, or, as an alternative, kinase-dead Src may recruit and/or activate other tyrosine kinases to target this tumor suppressor [56].…”
Section: Src-dependent Regulation Of Tumor Suppressorsmentioning
confidence: 99%